The quality of colostrum and vitality of calves, born from cows with different reaction to stress experiences - Chernenko, Oleksandr; Chernenko, O. M.; Chernenko, Oleksandr Mikolajovich; Chernenko, O.; Chernenko, Oleksandr M.; Chernenko, A.; Черненко, Олександр Миколайович; Chernenko, O.; Chernenko, O. I.; Chernenko, Olena Ivanivna; Черненко, Олена Іванівна; Sanzhara, R. A.; et al. (Oles Honchar Dnipropetrovsk National University, 2017)
The article presents the results of studying cortisol concentration and creatine phosphokinase activity in the blood serum of 40 half-sib Ukrainian black and white dairy cows an hour after planned blood extraction, which was a stress experience. We divided the cows into three groups according to the distribution of cortisol concentration in the animals: I – high, II – average and III – low stress resistance. During the research, the cows from these groups were in their fourth month of lactation after their first calving. They were kept untethered in their summer quarters, natural pastures. The aim of the research was to identify the differences in the quality of colostrum, the vitality of the calves up to the age of 6 months, the vitality of the mother-cows, and also the influence of their different adaptation potentials in cases of abortion and stillborn calves among the cows from different groups. At the dairy complex where the research was conducted, the quality of the cows’ colostrum is not monitored. This is typical for most dairy plants of Ukraine. We found that the classes of A and M immunoglobulins did not depend upon which particular groups the animals belonged to, whereas the content of immunoglobulins of class G is 6.7 g/l higher, and the content of total protein is 8.9 g/l higher in the yield of colostrum of the cows from group 1. The influence of cows’ different levels of resistance to stress experiences on their incidence of abortions and stillborn calves was not determined. Gastroenteritis occurred among calves of cows from group 3 three times more often than with those of group 1. Vitality of calves from cows of groups 1 and 2 was significantly higher. Therefore, technological stress experiences of mother-cows have a negative effect upon the quality of colostrum and upon the vitality of calves. This factor ought to be taken into consideration in the exploitation of animals, especially during pregnancy in order to minimise stress and help individuals with less strong nervous systems. Solving the complex problems of increasing the vitality of calves involves in part guaranteeing their provision with colostrum immunity by compulsory control of the colostrum’ quality using a special aerometer (Colostrometer). У статті представлено результати дослідження концентрації кортизолу та активності креатинфосфокінази в сироватці крові 40 напівсібних українських чорно-рябих молочних корів через годину після планового забору крові, що було стресовим досвідом. Корів ми розділили на три групи за розподілом концентрації кортизолу у тварин: I – висока, II – середня та III – низька стійкість до стресу. Під час дослідження корови з цих груп перебували на четвертому місяці лактації після першого отелення. Їх утримували без прив'язу на літніх пасовищах, природних пасовищах. Метою дослідження було виявити відмінності в якості молозива, життєздатності телят до 6-місячного віку, життєздатності корів-матерів, а також вплив їх різного адаптаційного потенціалу у випадках абортів та мертвонароджених телят серед корів з різних груп. На молочному комплексі, де проводилося дослідження, якість молозива корів не контролюється. Це характерно для більшості молочних заводів України. Ми виявили, що класи імуноглобулінів А та М не залежать від того, до яких конкретних груп належали тварини, тоді як вміст імуноглобулінів класу G на 6,7 г/л вищий, а вміст загального білка на 8,9 г/л вищий у виході молозива у корів 1-ї групи. Вплив різного рівня стійкості корів до стресових переживань на частоту абортів та мертвонароджених телят не визначено. Гастроентерит у телят корів 3-ї групи траплявся втричі частіше, ніж у телят 1-ї групи. Життєздатність телят корів 1-ї та 2-ї груп була значно вищою. Отже, технологічний стресовий досвід корів-матерів негативно впливає на якість молозива та життєздатність телят. Цей фактор слід враховувати при експлуатації тварин, особливо під час вагітності, щоб мінімізувати стрес та допомогти особам зі слабкою нервовою системою. Вирішення складних проблем підвищення життєздатності телят частково передбачає гарантування їхнього забезпечення імунітетом до молозива шляхом обов'язкового контролю якості молозива за допомогою спеціального аерометра (колостометра).
Якість молозива та життєздатність телят, народжених від корів з різною реакцією на стресові переживання
Черненко Олександр Миколайович https://orcid.org/0000-0002-8829-3148 Черненко Олена Іванівна https://orcid.org/0000-0002-5951-6576 Cанжара Роман Андрійович https://orcid.org/0000-0002-7660-2476
Keywords: content of protein; вміст білка; cortisol; кортизол; creatine phosphokinase; креатинфосфокіназа; adaptation potential; адаптаційний потенціал; immunoglobulins A and M; імуноглобуліни А та М